Moral Responsibility and Confidence as Factors that Influence Teacher Involvement in Educational Change - Cecilio López (Profile: Issues in Teachers' Professional Development)
Various factors that are not easily observed have a strong impact on educational change. In this paper, I examine some of the issues that emerged from the data collected while exploring my informants' perceptions and attitudes towards their changing roles when confronted with curriculum innovation. This research demonstrates that the experience teachers acquire during their career may often enable them to participate in the design of a new study plan. However, this experience does not always justify their role as curriculum-designers in either the eyes of their colleagues or in their own eyes, particularly when coerced into playing this or other roles. The results indicate that teachers, depending on their levels of moral responsibility and confidence, become involved in different roles during their teaching career.